HUBUNGAN ANTARA KONSEP DIRI DENGAN GAYA HIDUP HEDONIS PADA SISWA KELAS X SMA NEGERI 7 DEPOK - Al Fatihatul Ainun Salsabila; Dwi Dasalinda (LPPM Institut Pendidikan Nusantara Global, 2023)
This research is motivated by a preliminary study of the field based on the results of observations and interviews that researchers conducted with one of the students who had hedonic lifestyle behavior. The purpose of this study is to determine a relationship between self-concept and hedonistic lifestyle of class X students of SMA Negeri 7 Depok. This study uses a quantitative approach with a correlation method. The population in the study was 291 students. With the sample test results totaling 44 students with sampling techniques using simple random sampling where the sampling of sample members from the population is carried out randomly without regard to the strata in the population. The data collection technique was carried out using a questionnaire distributed to students using google form. This research technique has a normal and linear distribution. As for how to determine the relationship between variables x and y, researchers used parametric data analysis with the Moment Product Correlation test method. The results obtained with a significant -0.070 if r> 0.05 then it is stated that there is no relationship between variables x and y.